Pengaruh pemberian rumput laut sargassum sp terhadap kadar hemoglobin dan feritin serum - Yuniarti, Anita; Hadisaputro, Soeharyo; W, Nyoman Suci (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2016)
Background : Anemia is a global phenomenon involving developing countries. Fifty percent of anemia cases is caused by iron deficiency. Indonesia is a tropical country that is rich in various kinds of marine plants and still not used optimally.Sargassum sp is one of high iron contains seaweed but still less utilized. Objectives: the aim of this study was to analyze the influence of Sargassum sp on hemoglobin and serum ferritin level. Methods : a simple randomized with pre and posttest control group design was used in this study. Sixteen Wistar male rats were divided into 2 groups (1) control (2) treatment and fed with Sargassum sp 0,49 g for 14 days. During the treatment pre and post hemoglobin and serum ferritin was measured. Results : : iron level in Sargassum sp was 122,37mg/g and Pb level was 0,00009%. In the treatment group hemoglobin level was significantly increased 5,24 mg/dl (p<0,05) and serum ferritin was increased 4,20 Âµg/ml (p>0,05). Conclusion : sargassum sp increased hemoglobin level on anemic wistar rat but not in serum ferritin significantly.Â